Influence of the implementation of the ISO 45001:2018 Standard on the perception of safety and health of Geological Engineering students at the Universidad Nacional Mayor de San Marcos - Elescano Yupanqui, Juan Manuel (2023)
In this research, the influence of developing an Implementation Design of an Occupational Health and Safety Management System (OSH) was verified within the framework of the requirements of the ISO 45001:2018 Standard for the Professional School of Geological Engineering (EPIG) of the Universidad Nacional Mayor de San Marcos (UNMSM), its dissemination among students and the measurement of its direct impact on well-being, teaching and learning. This problem arises from the need to know health and safety standards in university academic environments as a priority of every educational institution, in which the impacts that the implementation of the requirements of this international standard in the institution could cause were evaluated; A baseline study was carried out on the School's SST management to have a reference point when measuring its influence when implementing this management system. To collect data for this research, the dissemination of the ISO 45001 standard and a design for the EPIG was carried out, via the Internet aimed at the entire student population. In a reasonable time, the capture of information was continued through a survey directed at a quantity of sample population made up of EPIG students. Finally, it was concluded that the development of an SST design based on the ISO 45001 Standard for the EPIG and its subsequent dissemination among students generates a perception of the direct influence for the benefit of the school's students as an interest group.